2013
DOI: 10.5433/1679-0359.2013v34n6supl2p3811
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência da erliquiose monocítica canina e anaplasmose trombocítica em cães suspeitos de hemoparasitose em Cuiabá, Mato Grosso

Abstract: ResumoO presente estudo avaliou a ocorrência da Erliquiose Monocítica Canina e Anaplasmose Trombocitotrópica Canina em 77 cães atendidos no Hospital Veterinário (HOVET) da Universidade Federal de Mato Grosso (UFMT) no ano de 2009, buscando associar à possíveis dados clínicos e hematológicos. Os cães foram avaliados pela amplificação parcial do genes dsb e 16S rRNA de Ehrlichia canis e Anaplasma platys e Reação de Imunofluorescência Indireta (RIFI) para E. canis. DNA de E. canis foi detectado em 18 (23,3%) e de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 18 publications
(32 reference statements)
3
10
0
9
Order By: Relevance
“…The coinfection of these agents is common, as both use the same vector for infection of the host (SANTOS et al, 2013). The occurrence of these pathogens is similar to that obtained by Witter et al (2013), who studied symptomatic canines within the same area. It is important to note that the canines in this study had no apparent clinical symptoms of the infection.…”
Section: Infection With B (Canis) Vogeli Was Identified Insupporting
confidence: 59%
“…The coinfection of these agents is common, as both use the same vector for infection of the host (SANTOS et al, 2013). The occurrence of these pathogens is similar to that obtained by Witter et al (2013), who studied symptomatic canines within the same area. It is important to note that the canines in this study had no apparent clinical symptoms of the infection.…”
Section: Infection With B (Canis) Vogeli Was Identified Insupporting
confidence: 59%
“…Melo et al (2011) reported a prevalence of 74.4% in urban and of 67.5% in rural dogs (overall frequency of 70.9%), whereas Witter et al (2013) informed a seroprevalence of 70.1%; in this last study the frequency of E. canis infection was of 23.3% by PCR. On the other hand, also in Brazil a prevalence of E. canis of 41.5% by IFA and of 9.4% was found in cats (Braga et al, 2014).…”
Section: Introductionmentioning
confidence: 46%
“…(57,1%) em relação à Anaplasma spp. (21,4%), divergindo dos achados de Ribeiro et al (13) , que analisaram 182 cães procedentes de Pato Branco ̶ PR e obtiveram 32,9% (60/182) de animais positivos para A. platys e todos negativos para E. canis, com base na Reação em Cadeia da Polimerase (PCR), assim como dos resultados obtidos por Witter et al (14) , que, utilizando a técnica de PCR associada à Reação de Imunofluorescência Indireta (RIFI), obtiveram 23,3% e 9,1% de animais reagentes para E. canis e A. platys, respectivamente, com base em análise realizada em 77 cães em Cuiabá − MT, além de 5,2% de coinfecção.…”
Section: Discussionunclassified
“…A divergência encontrada entre este estudo e os realizados por Ribeiro et al (13) , Witter et al (14) e Ramos et al (15) pode ser explicada principalmente pelo número e pelas características dos animais HOLANDA, L.C. et al…”
Section: Discussionunclassified